Mutations in Coagulation Factor VIII Are Associated with More Favorable Outcome in Patients with Cutaneous Melanoma - Ping, Zheng; Soni, Abha; Williams, Lance A., III; Pham, Huy P.; Basu, Malay K.; Zheng, X. Long (TH Open, 2017)
Coagulation factor VIII (FVIII), von Willebrand factor (VWF), and ADAMTS13 (a disintegrin and metalloprotease with thrombospondin type 1 repeats 13) play an important role in the regulation of normal hemostasis. However, little is known about their roles in patients with malignancy, particularly with cutaneous melanoma. Whole genome sequencing data are available for 25,719 cases in 126 cancer genomic studies for analysis. All sequencing data and corresponding pathology findings were obtained from The Cancer Genome Atlas. The cBioPortal bioinformatics tools were used for the data analysis. Our results demonstrated that mutations in genes encoding FVIII, VWF, and ADAMTS13 were reported in 92 of 126 cancer genomic studies, and high mutation rates in these three genes were observed in patients with cutaneous melanoma from three independent studies. Moreover, high mutation rates in FVIII, VWF, and ADAMTS13 were also found in patients with diffuse large B cell lymphoma (22.9%), lung small cell carcinoma (20.7%), and colon adenocarcinoma (19.4%). Among 366 melanoma cases from TCGA provisional, the somatic mutation rates of FVIII, VWF, and ADAMTS13 in tumor cells were 15, 14, and 5%, respectively. There was a strong tendency for coexisting mutations of FVIII, VWF, and ADAMTS13. Kaplan–Meier survival analysis demonstrated that melanoma patients with FVIII mutations had a more favorable overall survival rate than those without FVIII mutations (p = 0.02). These findings suggest, for the first time, that the FVIII mutation burden may have a prognostic value for patients with cutaneous melanoma. Further studies are warranted to delineate the molecular mechanisms underlying the favorable prognosis associated with FVIII mutations.
Keywords: coagulation factors; tumor metastasis; factor VIII; von Willebrand factor; ADAMS/ADAMTS13